2017
DOI: 10.1016/j.ejvs.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Centre Study on Cardiovascular Risk Management on Patients Undergoing AAA Surveillance

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…In this study of ten vascular centres in the UK the medical management of patients with PAD was suboptimal. Previous studies by VERN in the UK had highlighted that cardiovascular risk management in patients with aneurysms is suboptimal. Most patients in the present series were hyperlipidaemic and hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…In this study of ten vascular centres in the UK the medical management of patients with PAD was suboptimal. Previous studies by VERN in the UK had highlighted that cardiovascular risk management in patients with aneurysms is suboptimal. Most patients in the present series were hyperlipidaemic and hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Although rate of prescriptions for antiplatelet and statin agents are improving for patients with abdominal aortic aneurysm, 16 previous work by VERN has shown that those under aneurysm surveillance also have poor uptake of best medical therapy, 36 suggesting that both primary and secondary care must improve further. Future work must evaluate patient compliance in the long term with reducing cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by VERN has highlighted that advice given to patients on abdominal aortic aneurysm surveillance programmes is insufficient, with only 66% of patients given full cardiovascular risk reduction advice and only 82% of surveillance units advising changes to the patient's prescription. 36 Further work is required to determine uptake of this advice and compliance in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Its multidisciplinary structure fosters close links between trainee surgeons, nurses and vascular scientists on a national basis. VERN has successfully delivered several multi-centre audits without incurring cost using this collaborative approach [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%